1998
DOI: 10.1159/000028637
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Childhood Intracranial Ependymomas: The Role of Age and Tumor Location

Abstract: Despite several clinical reports on intracranial ependymomas in children, the factors which affect prognosis, and the possibility that certain combinations of factors might limit survival, are still a matter of debate. Between 1976 and 1996 we operated on 35 children with intracranial ependymomas. Postoperative irradiation was given to 27 patients, with associated chemotherapy in 6 cases. Mean follow-up was 62 months. In 12 patients a 5-year follow-up was possible. In October 1996, 18 patients (51.4%) were sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 32 publications
3
35
2
1
Order By: Relevance
“…Many studies had Grade II ependymomas that were up to two to three times more frequent than Grade III tumors. 3,4,6,9,11,14,15,17,20,22,24,25,30 In some studies this ratio was almost equal, 13,19,[33][34][35] while in others there were far more Grade III than Grade II ependymomas. 12,26,28,29,31,32 In one study of ependymomas in children under 5 years of age, the authors reported eight Grade II and 60 Grade III ependymomas.…”
Section: Pediatric Posterior Fossa Ependymomas T Tihan Et Almentioning
confidence: 96%
See 2 more Smart Citations
“…Many studies had Grade II ependymomas that were up to two to three times more frequent than Grade III tumors. 3,4,6,9,11,14,15,17,20,22,24,25,30 In some studies this ratio was almost equal, 13,19,[33][34][35] while in others there were far more Grade III than Grade II ependymomas. 12,26,28,29,31,32 In one study of ependymomas in children under 5 years of age, the authors reported eight Grade II and 60 Grade III ependymomas.…”
Section: Pediatric Posterior Fossa Ependymomas T Tihan Et Almentioning
confidence: 96%
“…Among 18 studies where the effect of age on survival was analyzed, 12 studies reported age at diagnosis as an independent prognostic factor. 4,7,[9][10][11]13,20,22,24,25,33,34 Six of these studies considered the cut-off for age groups as 3 years, two as 4 years, and one as 5 years of age. In one study, age was calculated as a continuous variable, and in another study of children younger than 3 years, the cut-off between two age groups was 2 years of age (24 months).…”
Section: Pediatric Posterior Fossa Ependymomas T Tihan Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, children below 3 years of age and infratentorial ependymomas have been associated with a poor outcome (6,(22)(23)(24). It remains unclear whether this reflects tumor biology, the surgical inaccessibility of posterior fossa tumors, which are more prevalent in younger children, or the avoidance of adjuvant radiotherapy in early life resulting from concerns about long term clinical sequelae (4,14,23,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) classification of these tumors, based on histology, divides them into grade I (myxopapillary), grade II (conventional), and grade III (anaplastic) ependymomas. Histologic grading of these tumors does not predict clinical behavior as accurately as other gliomas, [1][2][3][4][5][6] although there are some studies that show a significant association between tumor grade and prognosis. [7][8][9][10] Thus far, the only consistent prognostic variables include extent of surgical resection, with tumor location and patient's age also having some significance.…”
mentioning
confidence: 91%